6 - The Politics Of Infrastructural Provision in Rural Areas of Oyo State Nigeria - Ayobami Abayomi Popoola, (African Sociological Review, 2022)
Over the years, rural service delivery is often subjected to political players and less of the rural public interest. The study examined rural people experiences of local government rural LGAs of Oyo state, Nigeria. The concept of governance provides the conceptual balance for this study. The study made use of a mixed approach for data collection, qualitative and quantitative tools of questionnaire and in-depth interview respectively. Two hundred and fifty (250) rural households across six (6) LGAs were administered questionnaire randomly from the purposively identified rural local government areas. Study revealed that infrastructure politicking is a challenge that limits sustainable rural facility delivery. This is because infrastructures such as water infrastructure, school buildings and drainage construction were provided based on political affiliation. Over half of the respondents consider rural governance not to be participatory and inclusive towards rural development. The study recommends that democratic local government autonomy remains the feasible and responsive solution to efficient service delivery in the local space.